The effect of endoscopic sinus surgery on mucociliary activity and healing of maxillary sinus mucosa - (:unkn) unknown (INT RHINOLOGIC SOC, 2000)
The aim of this study was to determine histologic findings in the maxilaarysinus mucosa by scanning electron microscopy (SEM) and transsmission electron microscopy (TEM), and ciliary activity within the nasal cavity by measuring the speed of mucociliary transport and after endoscopic sinus surgery (ESS). Thirty patients were enrolled. Thirtyeight antral mucosae of 24 24 patients were investigated according to ultrastructural changes and 6 patients were accepted as controls. At the 12th week, 12 antral nasal mucosae specimens of 8 patients were evaluated. AN the specimens were taken from the medial rear wall of the antrum. The specimens were observed under a SEM and TEM. The mucociliary activity was measured within the nasal cavity by a saccharin test in all patients before the operation and after 12 weeks. Twenty people served as controls. In the specimens of the preoperative mucosa, the ciliated epithelium was heavily deciliated, interdigitation of the cell was loosened. In the samples taken 12 weeks after the operation, the ciliated cells were irregularly seen, the number of goblet cells was about the same as in the preoperative group and in the control, the number of the gland openings was higher than in the preoperative group and in the control. Also the interdigitation of the cells was enhanced. The histological and morphological features of the mucosa had improved. The period of the preoperative saccharin test was 12.15 minutes, whereas the period of the postoperative test was 9.08 minutes. The improvement was significant but both results were also significantly longer compared to the controls. These obervations suggest that the histological, morphological and mucocilliary activity of the mucosa have not yet improved completely, it cakes more than 12 weeks to recover, and the patients should be closely monitored in the postoperative months.
Keywords: endoscopic sinus surgery; mucociliary activity; scanning and transmission electron microscopy; healing; follow-up; RABBITS; REGENERATION; CLEARANCE